Impact of extracurricular factors on the academic performance of university students during the COVID-19 pandemic - Sanz, Maria T.; López-Iñesta, Emilia (Frontiers in Education, 2022)
This paper aims to study the incidence of extracurricular factors relating to a) personal work situation and place of residence; b) family finances; and c) access to the virtual environment on the academic results of university students during the COVID-19 pandemic. Regression models were used to determine the impact of the different factors on academic performance in a sample of 138 students of the Primary Education Teaching Degree at a Spanish public university. The results show that students who devote themselves wholly to studying without having to work obtain better academic results than those who have to combine study and work. Furthermore, internet access affects academic results, with students having ADSL and Wi-Fi via smartphones reporting the highest grades.